2017
DOI: 10.1111/dth.12481
|View full text |Cite
|
Sign up to set email alerts
|

The role of nicotinamide in acne treatment

Abstract: Safe and effective treatment options for acne vulgaris are needed to address side effects and increasing rates of antibiotic resistance from current treatments. Nicotinamide is a vitamin with potent anti-inflammatory properties that could offer a potential treatment option. We aim to summarize the relevant literature on the role of nicotinamide in acne vulgaris and discuss the next steps necessary to move this approach into clinical practice. We searched PubMed for clinical studies using nicotinamide for treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 26 publications
(38 reference statements)
0
33
0
Order By: Relevance
“…The androgenic character makes human adrenal NCI‐H295R cells a good model to study androgen biosynthesis as they produce more androgen in a starvation state . NAM plays roles in the treatment of acne vulgaris and the development of diabetes but its effects on androgen production is unknown . Using this ideal cell model, we found that NAM not only inhibits cell viability but also reduces testosterone production in starved NCI‐H295R cells at high doses.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The androgenic character makes human adrenal NCI‐H295R cells a good model to study androgen biosynthesis as they produce more androgen in a starvation state . NAM plays roles in the treatment of acne vulgaris and the development of diabetes but its effects on androgen production is unknown . Using this ideal cell model, we found that NAM not only inhibits cell viability but also reduces testosterone production in starved NCI‐H295R cells at high doses.…”
Section: Discussionmentioning
confidence: 96%
“…12 NAM plays roles in the treatment of acne vulgaris and the development of diabetes but its effects on androgen production is unknown. 5,13,14 Using this ideal cell model, we found that NAM not only inhibits cell viability but also reduces testosterone production in starved NCI-H295R cells at high doses. The reduced cell viability might affect the total testosterone production, although the androgen synthetic ability of adrenal cells was also reduced.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The authors were specific to call out that Nam is not considered to be a hair growth promoter. Although the authors reported data that 0.1% Nam treatment had a statistically significant increase in hair thickness and density when compared to baseline, it is difficult to conclude that 0.1% Nam actually had a relevant effect on hair biology properties for the following reasons: (1) the lack of a placebo control renders the conclusions non-relevant that Nam can stimulate hair growth because it is well known that a placebo treatment can have a directionally positive effect on hair growth [3]; (2) 0.1% Nam is an order of magnitude lower in concentration than what is typically tested in dermatology-related studies [4,5]. Minoxidil, one of the only two FDA-approved hair growth molecules, needs to be applied at 2-5% to attain efficacy.…”
Section: Topical Niacinamide Does Not Stimulate Hair Growth Based On mentioning
confidence: 99%